Reactive guardianship: Who intervenes? How? And why? - Barnum, Timothy C. (Criminology, 2024)
Guardianship is a core tenet of routine activity theory and collective efficacy. At its outset, routine activity research assumed that the mere presence of a guardian was sufficient to disrupt many forms of crime. More recent research, however, has taken as a starting point that would-be-guardians must take on an active role for a reduction in crime to occur. Integrating research on bystander intervention and guardianship-in-action, the current study elaborates the individual-level motivations and decision processes of guardianship to answer the following questions: Who serves as a reactive guardian? How do they do so? And why? We tasked young adults (N = 1,032) included in the recent waves of the Zurich Project on the Social Development from Childhood to Adulthood (z-proso) to assess a 70-second video depicting a sexual harassment event. We examined participants’ willingness to engage in a range of intervention options as a function of their prosocial attitudes, safety considerations, socioemotional motivations, and moral considerations. Results show a complex decision process leading to whether and how a would-be guardian decides to intervene to disrupt sexual harassment, such that prosocial motivations and emotional reactions are weighed against perceptions of danger when deciding on a specific course of action.